European evidence for the representation of the woolly rhinoceros in art - Pawłowska, Kamilla; Pogoda, Zofia; Lao, Diego Jaime Alvarez; Codrea, Vlad; Kolfschoten, Thijs van; Dedła, Kajetan; Croitor, Roman (My University, 2026)
In this work, we focus on art featuring woolly rhinoceroses from the Eurasian continent. We will provide an overview of cave paintings, engravings, and other evidence of art in terms of (i) geographic scope, (ii) chronology, (iii) representation, (iv) associated fauna, (v) material and technique used, and (vi) creator. Since rhinoceros and birds presently constitute a shared landscape, we examined the links between fossil rhinos and birds and other animals in the evidence of Paleolithic art. We found that rhinoceroses make a minor contribution (2.6 %) to Paleolithic art. Evidence comes from France, Belgium, Czech Republic, Germany, Slovakia, Spain, Romania, and Russia and is attributed to the Aurignacian, Gravettian, Solutrean, and Magdalenian cultures. The animal is usually shown alone or co-occurring with woolly mammoths and other fauna. The depictions are not juxtaposed with birds, contrary to the present state of affairs. This is due to the presence of fur on the rhinoceros and the climatic demands of birds. The rhinoceroses are shown superficially as an outline and in detail with a hump, with a black stripe, bleeding, or fighting one. These paintings woolly rhinoceroses can be linked to modern humans who used charcoal, ochre and manganese oxides to represent them in the artworks. Engravings of woolly rhinoceroses also occur on mobile objects such as reindeer antlers and rock slabs.
Keywords: woolly rhinoceros; art; paintings; Pleistocene; Paleolithic; Europe